2016
DOI: 10.1073/pnas.1611882113
|View full text |Cite
|
Sign up to set email alerts
|

PAXX and XLF DNA repair factors are functionally redundant in joining DNA breaks in a G1-arrested progenitor B-cell line

Abstract: Classical nonhomologous end joining (C-NHEJ) is a major mammalian DNA double-strand break (DSB) repair pathway. Core C-NHEJ factors, such as XRCC4, are required for joining DSB intermediates of the G1 phase-specific V(D)J recombination reaction in progenitor lymphocytes. Core factors also contribute to joining DSBs in cycling mature B-lineage cells, including DSBs generated during antibody class switch recombination (CSR) and DSBs generated by ionizing radiation. The XRCC4-like-factor (XLF) C-NHEJ protein is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
111
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 39 publications
(62 reference statements)
13
111
0
Order By: Relevance
“…[8][9][10] Interestingly, asynchronous PAXXdefective CH12 B-cell lines or v-Abl-transformed Pro-B-cell lines do not demonstrate any IR sensitivity above that of their wt counterparts, as we found in MEFs, and the concomitant PAXX and Xlf deficiency does not worsen the sensitivity caused by Xlf mutation alone in these cycling cells. 13 In contrast, the synchronization of PAXX −/− /Xlf − / − v-Abl pro-B cells into the G1 phase of the cell cycle with either STI-571 (vAbl kinase inhibitor) or PD033991 (CDK4/6 inhibitor) results in an extreme sensitivity to IR, well beyond that of Xlf − / − single mutants in the same conditions arguing for a unique role of PAXX in classical NHEJ when DNA damage occurs in G1, hence in the absence of functional HR. Our observation of an IR sensitivity of small resting, ex vivo purified T lymphocytes from PAXX − / − mice concords with this conclusion of a specific role of PAXX during C-NHEJ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10] Interestingly, asynchronous PAXXdefective CH12 B-cell lines or v-Abl-transformed Pro-B-cell lines do not demonstrate any IR sensitivity above that of their wt counterparts, as we found in MEFs, and the concomitant PAXX and Xlf deficiency does not worsen the sensitivity caused by Xlf mutation alone in these cycling cells. 13 In contrast, the synchronization of PAXX −/− /Xlf − / − v-Abl pro-B cells into the G1 phase of the cell cycle with either STI-571 (vAbl kinase inhibitor) or PD033991 (CDK4/6 inhibitor) results in an extreme sensitivity to IR, well beyond that of Xlf − / − single mutants in the same conditions arguing for a unique role of PAXX in classical NHEJ when DNA damage occurs in G1, hence in the absence of functional HR. Our observation of an IR sensitivity of small resting, ex vivo purified T lymphocytes from PAXX − / − mice concords with this conclusion of a specific role of PAXX during C-NHEJ.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][12][13][14][15] This suggested a possible functional complementation of PAXX deficiency in certain conditions.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Both XLF and PAXX share structural similarity with XRCC4 (62,64). Individual XLF and PAXX mutants display only a mild phenotype, but XLF PAXX double mutants are synthetically lethal in mice and reduce V(D)J recombination in human B lymphocytes (98)(99)(100)(101), suggesting that while they may be redundant, at least one is necessary for efficient repair by NHEJ. The main purpose of XLF and PAXX appears to be in providing additional structural support to stabilize two DNA ends, thereby enhancing the ability of XRCC4·Lig4.…”
Section: Xlf and Paxx Stimulate Ligation By The Xrcc4·lig4 Complexmentioning
confidence: 99%
“…Due to the extensive cell death in lymphoid progenitors in developing embryos, we were unable to isolate B cells from Paxx −/− Xlf −/− mice to examine their radiosensitivity in vitro. However, recent data using Paxx/Xlf single-knockout and double-knockout v-Abl transformed pro-B cells derived from wild-type mice demonstrated that, in this cell lineage as in the developing CNS, a synthetic relationship between PAXX and XLF exists in terms of cellular sensitivity to IR as well as in the process of V(D)J recombination (Kumar et al 2016;Lescale et al 2016b). Thus, there appears to be a tissue-specific requirement for PAXX and XLF: In some cells, both PAXX and XLF are required for NHEJ, but, in others, either one or the other suffices to a major degree.…”
Section: Xlfmentioning
confidence: 99%